1991
DOI: 10.1001/archderm.1991.01680070067007
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor a Expression Helps to Distinguish Keratoacanthomas From Squamous Cell Carcinomas

Abstract: Keratoacanthomas may be difficult to distinguish histologically from squamous cell carcinomas. We studied 20 keratocanthomas and 22 squamous cell carcinomas immunohistochemically using an antibody directed against transforming growth factor alpha to determine if the pattern of transforming growth factor alpha expression would provide a useful method of differentiating these tumors. Ninety percent of the keratoacanthomas demonstrated a diffuse pattern within tumor lobules in which all but the most peripheral ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 37 publications
(3 reference statements)
0
8
0
1
Order By: Relevance
“…A similar pattern has been described in cutaneous keratocanthomas. 24 25 Grandis et al, in their studies of squamous cell carcinomas of the head and neck region, have shown that both the neoplastic and non-neoplastic mucosa show an upregulation in synthesis of TGF-and EGFR which may explain the frequent synchronous and metachronous malignancies of that mucosa, although the excess synthesis of these molecules is apparently not limited to hyperplastic mucosa in their material. 19 20 Our findings indi-cate that increased expression of TGF-and EGFR is a feature of early stages in neoplastic transformation of squamous epithelium, and TGF-/EGFR positive hyperplastic keratinising squamous metaplasia is possibly the earliest manifestation of that functional state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar pattern has been described in cutaneous keratocanthomas. 24 25 Grandis et al, in their studies of squamous cell carcinomas of the head and neck region, have shown that both the neoplastic and non-neoplastic mucosa show an upregulation in synthesis of TGF-and EGFR which may explain the frequent synchronous and metachronous malignancies of that mucosa, although the excess synthesis of these molecules is apparently not limited to hyperplastic mucosa in their material. 19 20 Our findings indi-cate that increased expression of TGF-and EGFR is a feature of early stages in neoplastic transformation of squamous epithelium, and TGF-/EGFR positive hyperplastic keratinising squamous metaplasia is possibly the earliest manifestation of that functional state.…”
Section: Discussionmentioning
confidence: 99%
“…28 This fact also underlines the need to examine biopsy material to look for the extent of expression of EGFR before such treatments are contemplated. Since interaction between growth factors and their ligands is often very complex, this hypothesis needs to be confirmed in a larger prospective study that should include investigations of tumour suppressor genes, proliferation markers, and other modulators of eVects of TGF-such as TGF-, 24 as well as survival data.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported diffuse distribution of transforming growth factor‐a (TGFa) in the majority of KA. Forty per cent of SCC exhibit a focal enrichment of TGFa whereas 90% of KA exhibit no staining in this area .…”
Section: Discrimination: Ka Versus Sccmentioning
confidence: 97%
“…[4][5][6][7][8] However, most authors emphasize that KA is easily confused with welldifferentiated SCC, and several authors consider KA a variant of SCC. [9][10][11] Further studies correlated the histopathologic features, with the aid of a certain tool, [11][12][13][14][15][16][17][18][19][20] to establish a KA diagnosis, but in those works, no correlation with the biologic course was given. The benign clinical course of KA allows clear distinction from SCC.…”
mentioning
confidence: 99%